Capitalisms compared welfare, work, and business - Bowman, John R. 1952- (Sage/CQ Press, 2014)
A brief supplemental text for upper level undergraduate courses in comparative political economy, comparative public policy, and American political economy. The book's six chapters look in detail at the political economies of the U.S., Sweden and Germany, exploring the fundamental differences between their handling of health policy, pensions, family policy, corporate governance and fiance, and labor markets. The book's many rich and well rendered examples of the three countries' various policies helps students push past abstractions and understand what it is actually like to live under different capitalist systems
Keywords: Capitalism -- Case studies; Policy sciences -- Case studies; Comparative economics; Wohlfahrtsstaat; Kapitalismus; Deutschland; Schweden; USA; Fallstudiensammlung